KETERLIBATAN AUDITOR DALAM DETEKSI DAN PEMULIHAN KECURANGAN - Idayu, Riyanthi; Husni, Mohamad (National Conference on Applied Business, Education, & Technology (NCABET), 2024)
This research discusses the role and involvement of auditors in the process of detecting and recovering from fraud, which is a crucial aspect of maintaining the integrity of financial statements and creating a transparent and accountable business environment. Auditors have a significant responsibility in detecting indications of fraud through the application of specific audit methods, such as forensic testing, data analysis, and in-depth interviews. Additionally, with the support of increasingly sophisticated analytical technology, auditors can now utilize data analysis tools and artificial intelligence to identify patterns and anomalies that may indicate the presence of fraud. However, the role of auditors in fraud recovery tends to be more limited, as they are usually not directly involved in recovery actions, but rather provide reports and recommendations to management and the audit committee. Although auditor involvement has a positive impact in identifying and reducing fraud risk, challenges such as the limited scope of audits, potential conflicts of interest, and reliance on documentation provided by management can affect the effectiveness of this role. This research highlights the importance of company policies that support transparency and enabling technology so that auditors can be more effective in performing their roles. The research results indicate that auditor involvement in fraud detection and recovery significantly contributes to the improvement of corporate governance and the protection of stakeholder interests